REKONSTRUKSI JIHAD DALAM TAFSIR IBN ‘AJĪBAH: STUDI ATAS TAFSĪR AL-BAḤR AL-MADĪD FĪ TAFSĪR AL-QUR’ĀN AL-MAJĪD - Muhammd Muslihin (Tanzil: Jurnal Studi Al-Quran, 2023)
The essence of jihad as a doctrine that has an orientation to present the ethical system of a group of people who are awareof the importance of justice is often not created, this cannot be denied because of the stagnation that occurs when reading the Qur'an only prioritizing textuality. This gap gives rise to behaviors that seem anarchic, intolerant, and destructive. Therefore, to encourage a contextual, dynamic and tolerant interpretation of jihadist verses, deradicalization efforts are needed, and one of these efforts is the dissemination of religious literature that supports this spirit. Sufis are one of the groups that formulate interpretations of jihad verses with peaceful meanings. This research tries to raise Ibn ‘Ajībah's interpretation of jihad verses in his book Al-Baḥr Al-Madīd fī Tafsīr Al-Qur`ān Al-Majīd. The author reveals the essence and method of interpreting verses about jihad in Al-Baḥr Al-Madīd fī Tafsīr Al-Qur`ān Al-Majīd, as well as their significance for deradicalization efforts, which means for the understanding of religious texts in Indonesia today. Ibn ‘Ajībah's view of jihad can be summed up in two ways, namely the meaning of peaceful jihad and the meaning of armed jihad. In other words, Ibn ‘Ajībah's reading uses the irfān epistemology, based on the bayān epistemology. The significance of the verses of Jihad in Al-Baḥr Al-Madīd fī Tafsīr Al-Qur`ān Al-Majīd can be seen in terms of its method and content. From a methodological point of view, Ibn ‘Ajībah's interpretation is important because it offers an open, contextual model of meaning. In terms of content, Ibn ‘Ajībah's interpretation of jihad verses shows that jihad is not something revolutionary and radical, its meaning is very important to inform the public that jihad means more than just war and violence.